Sustainable Starch Strategies: Nano and Macro Adsorbents for the Detoxification of Synthetic Dyes and Heavy Metals - Wajeeha Naeem; Fazal Haq; Hashmat Ullah; Abid Khan; Rabia Kundi; Irum Bukhari; Iffat Ayesha Khan; Mehwish Kiran; Arshad Farid (Sustainable Chemical Engineering, 2024)
The research being conducted explores environmentally friendly techniques for the detoxification of heavy metals and synthetic dyes from aquariums using nano- and macro-adsorbents based on starch. In response to the urgent demand for sustainable wastewater treatment solutions, the research focuses on the development and evaluation of starch-based materials with enhanced adsorption capabilities. The effectiveness of macro-and nano-sized starch composites and starch-based adsorbents in facilitating the removal of heavy metals and synthetic dyes is evaluated. The review includes a thorough examination of equilibrium characteristics, kinetics, and adsorption mechanisms, and also considers how these sustainable starch-based products could be applied in real-world environmental remediation scenarios. The findings provide valuable insights into the development and implementation of starch-based adsorbents for the long-term, effective detoxification of heavy metals and synthetic dyes from water.